PENGARUH PENEMPATAN KERJA, GAYA KEPEMIMPINAN DAN PENGEMBANGAN KARIR TERHADAP BURNOUT KARYAWAN STATION NINJA XPRESS SIBOLGA - Danu Irwani Zelani; Endang Basaria Hutagalung; Ikmal Ikmal; Leyla Doriati Sitanggang; Mata Tias Zendrato (Jurnal Prodi Fakultas Ekonomi-UISU, 2022)
The formulation of the problem in this study is whether work placement, leadership style and career development simultaneously have a negative effect on employee burnout at Station Ninja Xpress Sibolga. This study aims to determine the effect of work placement, leadership style and career development on employee burnout at Station Ninja Xpress Sibolga. The sample in this study were employees at Station Ninja Xpress Sibolga, totaling 42 people. The data analysis technique in this research is Multiple Linear Regression. The results of this study indicate; Work placement partially has a negative effect on employee burnout; Leadership style partially has a negative effect on employee burnout; Career development partially has a negative effect on employee burnout; Work placement, leadership style and career development simultaneously have no positive and significant effect on employee burnout